Implementasi program kesehatan lingkungan dalam mengurangi kasus Demam Berdarah Dengue - Afandi, Salsabila Tsuraya (Maliki Interdisciplinary Journal, 2024)
Dengue hemorrhagic fever (DHF) is an infectious disease caused by the dengue virus and transmitted by the Aedes aegypti species mosquito. The role of vectors in the spread of disease can cause many cases to occur during the rainy season, where there are many puddles of water which become breeding grounds for mosquitoes. Apart from climate and environmental conditions, several studies show that dengue fever is associated with movement and population density as well as community behavior. Several factors that influence this are the basis for efforts to prevent and control dengue fever. The aim of this research is to provide an overview of the implementation of environmental health programs to reduce cases of dengue hemorrhagic fever. In this research, qualitative methods were used, which were obtained from journals and research results that had been carried out by previous researchers. The objects used are people who experience environmental programs. Rondinelli's policy implementation process theory is used in this research. There are four factors that can influence program performance, namely environmental conditions; relationships between organizations; organizational resources; and the characteristics and capabilities of implementing agencies. Facts on the ground show that the dengue fever control program is generally well implemented in the surrounding community, but there are several problems, especially related to organizational resources.